2014
DOI: 10.3390/molecules191118828
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Glycoxidation of Bovine Serum Albumin by Glucose, Fructose and Ribose and Its Prevention by Food Components

Abstract: Abstract:The aim of this study was to compare the kinetics of the glycoxidation of bovine serum albumin (BSA) as a model protein by three sugars: glucose, fructose and ribose, using fluorometric measurements of the content of advanced glycation end products (AGEs), protein-bound fructosamine, dityrosine, N'-formylkynurenine, kynurenine, tryptophan, the content of advanced oxidation protein products (AOPP), protein carbonyl groups, as well as thiol groups. Moreover, the levels of glycoalbumin and AGEs were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 41 publications
6
90
1
3
Order By: Relevance
“…Since AR induces EMT marker expression, there would be an increased risk of PCO formation after diabetic cataract removal. In an potentially related area, it is interesting to note that fructose, the end product of AR polyol pathway, has been demonstrated to form advanced glycated end-products (AGEs) much faster than glucose [35]. Raghavan and colleagues recently reported that AGEs in lens capsule enhance EMT of LECs under TGF-β2 treatment [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Since AR induces EMT marker expression, there would be an increased risk of PCO formation after diabetic cataract removal. In an potentially related area, it is interesting to note that fructose, the end product of AR polyol pathway, has been demonstrated to form advanced glycated end-products (AGEs) much faster than glucose [35]. Raghavan and colleagues recently reported that AGEs in lens capsule enhance EMT of LECs under TGF-β2 treatment [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…In the diabetic eye, cataract [52] and retinopathy [53] are major complications causing vision loss. Other than oxidative stress, AR polyol pathway also accelerates advanced glycation end-product (AGE) formation by producing fructose, which forms AGE much faster than glucose [54]. A study observed the increase of AGE in retina causes ocular inflammation by inducing RMG activation [19].…”
Section: Discussionmentioning
confidence: 99%
“…2, 9 These reactive carbonyl species (RCS), also knowns as AGE precursors, are much more reactive than reducing sugars. 10, 11 By continuing to react with proteins, these RCS irreversibly bind to the side chains of proteins, induce protein crosslinks, and lead to the formation of AGEs. While in general, RCS play a critical step in AGEs formation, glycation can also be catalyzed by free radicals and transition metals through oxidation.…”
Section: Introductionmentioning
confidence: 99%